The Influence Of Price, Service Quality, And Product Quality On Purchase Decisions Mediated By Purchase Intention (Empirical Study: Kriss Store Consumers In Tangerang Regency) - Sheren Lowinsky Jaya; Andreas Heryjanto (Publikasi Indonesia, 2023)
This study aims to determine the effect of price, service quality, and product quality on purchasing decisions mediated by purchase intention (empirical study: consumers at Kriss stores in Tangerang District). The research data was acquired from distributing questionnaires through the Google form. In taking samples, the study employed a Purposive sampling technique. This study used 150 respondents as the sample. This study applied quantitative analysis techniques and processed by SmartPLS. The test results show: 1) Price quality has a positive and significant effect on purchasing decisions, 2) Service quality has no positive and significant effect on purchasing decisions, 3) Product quality has a positive and significant effect on purchasing decisions, 4) Price has a positive but not significant effect on purchase intention, 5) Service quality has a positive but not significant effect on purchase intention, 6) Product quality has a positive and significant effect on purchase intention, 7) Purchase intention has a positive and significant effect on purchase decision, 8) Purchase intention does not mediate the relationship between price and decision purchase, 9) Purchase intention does not mediate the relationship between service quality and purchase decision, 10) Purchase intention does not mediate the relationship between service quality and purchase decision.